The Influence of Leverage on Audit Delay with Firm Size as a Moderating Variable - Putu Ayu Anggya Agustina; I Kadek Bagiana (Universitas Batanghari Jambi, 2023)
Regulation of POJK Number 29/POJK.04/2016 states that issuers or public companies are required to submit an annual report to the Financial Services Authority no later than the end of the fourth month after the end of the financial year (120 days). However, not all public accounting firms can complete the audit on time. One of the reasons, for it because the firms commits fraud or experiences financial difficulties. The purpose of this study is to prove the effect of leverage on audit delay with firm size as a moderating variable. This study uses the food and beverage industry in IDX in the 2016 to 2020. This research method is causal associative research using a quantitative approach. The number of samples is 35 observations. The data analysis technique used is Moderated Regression Analysis (MRA). The results is firm size is able to moderate the effect of leverage on audit delay.